The expanding world of extracellular traps: not only neutrophils but much more - Goldmann, Oliver; Medina, Eva (Frontiers in Immunology, 2013)
The release of extracellular traps (ETs) is a recently described mechanism of innate immune response to infection. Although ETs have been intensely investigated in the context of neutrophil antimicrobial effector mechanisms, other immune cells such as mast cells, eosinophils, and macrophages can also release these structures. The different ETs have several features in common, regardless of the type of cells from which they originated, including a DNA backbone with embedded antimicrobial peptides, proteases, and histones. However, they also exhibit remarkable individual differences such as the type of sub-cellular compartments from where the DNA backbone originates (e.g., nucleus or mitochondria), the proportion of responding cells within the pool, and/or the molecular mechanism/s underlying the ETs formation. This review summarizes the knowledge accumulated in recent years regarding the complex and expanding world of ETs and their role in immune function with particular emphasis on the role of other immune cells rather than on neutrophils exclusively.